Влияние внешней среды на рынок игристых вин - Поберейко, М. Н.; Кулиш, Татьяна Владимировна; Куліш, Тетяна Володимирівна; Kulish, Tetiana (ИжГТУ имени М.Т. Калашникова, 2015)
RU: В статье рассмотрено влияние внешней среды на рынок игристых вин, исследования со-временного состояния макро- и микросреды на рынке игристых вин в условиях функционирования виноградарско-винодельческой отрасли в рыночных условиях. Выявлены проблемы на рынке игристых вин и альтернативы их решения для качественного функционирования предприятий. Обоснованы альтернативы развития рынка в области виноделия. EN: The article considers the influence of the environment on the market of sparkling wines, the study of the current status of macro- and micro- market of sparkling wines in the functioning of grape and wine industry in market conditions. The specific problems on the market of sparkling wines were identified and their alternative solutions for the proper functioning of its businesse were suggesteds. Alternative solutions market development in the field of winemaking were proven.
Environmental influence on sparkling wines’ market
Keywords: внешняя среда; рынок игристых вин; винодельческая отрасль; игристое вино; альтернативы развития; external environment; the market of sparkling wines; wine industry; sparkling wine; alternative development